Assessment of interaction effect of deficit drip irrigation scheduling and agri-horti system on growth attributes, productivity and quality parameters of Indian mustard under semi-arid region - Anamika Barman; V.K. Singh; S. S. Rathore; Subhash Babu; P. K. Upadhyay; Rajiv Kumar Singh; Priyanka Saha (Annals of Agricultural Research, 2022)
Adoption of suitable agri-hortisystem (AHS) and different level of deficit irrigation scheduling (DIS) can improve growth attributes and productivity of Indian mustard under residual soil moisture of semi-arid region. A field experiment was conducted in rabi season in the year 2020-21 at research farm of ICAR-Indian Agricultural Research Institute to evaluate the interaction effect of AHS with three different levels of deficit irrigation scheduling via drip on growth, productivity and quality parameters of Indian mustard. Various suitable Agri-Horti Systems viz. moringa (Moringa oleifera L.), karonda (Carissa carandas L.), phalsa (Grewia asiatica L.), aonla (Phyllanthus emblica L.) and guava (Psidium guajava L.) were taken with different level of deficit irrigation viz. 0.6 IW/CPE, 0.4 IW/CPE and rainfed under sandy loam soil. The results revealed that the interaction effect of 0.6 IW/CPE treatment with moringa based AHS outperformed the others treatment combination. The interaction effect of Moringa based AHS × 0.6 IW/CPE had significant effect on plant height, number of primary and secondary branches. However, interaction effect between AHS and DIS for growth attributes viz. plant height, number of primary and secondary branches did not differ significantly for different AHS under rainfed and 0.4 IW/CPE DIS. The interaction effect between AHS and DIS on seed, stover and biological yield showed significant difference among the treatments. Quality parameters viz. oil content(%) as well as oil yield (kg ha-1) was recorded highest with the treatment combination of moringa with 0.6 IW/CPE.